Psychometric properties of the New Ecological Paradigm Scale (NEP) - Vdović Milica; Hagen Mina; Simonović Anja; Avramović Nađa; Milošević-Đorđević Jasna (Psihološka Istraživanja)
Climate change is a growing threat to humanity. Coping with its potentially disastrous effects will require a widespread behavioural change at both the societal and individual levels. Theory and empirical research have emphasised the role of pro-environmental attitudes as antecedents of pro-environmental behaviour. Using a large community Serbian sample (N=871 of adult population), assessed with face-to-face interviews, we searched for the psychometric characteristics of the New Ecological Paradigm scale (NEP), a widely used instrument for assessing the pro-environmental attitudes worldwide. The dimensionality of Dunlap's NEP scale has been called into question frequently, because previous studies revealed three, four, or only one dimension. Hence, there is an ongoing call for the scale's further validation. This has been the first time that the psychometric characteristics of the NEP scale were tested on a large adult sample in Serbia. Further, we tested its predictive power to explain environmental behaviour (using the Environmental Behaviour Questionnaire).